If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12(2e+3)=96
We simplify the equation to the form, which is simple to understand
12(2e+3)=96
Reorder the terms in parentheses
+(+24e+36)=96
Remove unnecessary parentheses
+24e+36=+96
We move all terms containing e to the left and all other terms to the right.
+24e=+96-36
We simplify left and right side of the equation.
+24e=+60
We divide both sides of the equation by 24 to get e.
e=2.5
| -4z-5=8z+3 | | C=20n+8 | | (2z+9)(7-z)=0 | | f(x)=-8x^2+8x+9 | | y=x^2ln(3x) | | n+33=25 | | y=3*(-3)+10 | | -7r=7(8+3r) | | 5ksquared=180 | | x^2+4x-20y+50=0 | | 7t-8=7+t | | m-48=-18 | | -x+7=-26+2x | | 3.92*1000000000000= | | (x-2)[2x-2(3+x)]-12= | | x^3+8x^2+19x+12=0 | | x+5*(3x+10)=2 | | s^3+8s^2+19s+12=0 | | 5+49x=28x+32 | | 1.68*100000000= | | 6a(-2a+3)= | | 6m-1=-4+5m | | (-x+9)(-8-11x)=0 | | z+16=33 | | 2h+6=56 | | -(3x-5)-(2x-6)+1=-(12x+5)-(3x+2)+3 | | 7.68x+4=58.9824+2x | | -7u=-28 | | (4-9x)(2-5x)=0 | | b-a=-5 | | m^2+9=73 | | 8.8a+14=119.6 |